How to identify the strategic alignment of teams with respect to project timeframe: a belief system approach for project-based alliances - Piccoli, Marcella Soares (2024)
This research explores the complex and dynamic world of Project-Based Alliances in the construction industry, unveiling a revolutionary artefact rooted in Robert Simons' Levels of Control, with a special focus on the Belief System to drive strategic team alignment. This qualitative study offers a unique perspective, delving into the intricate interplay between organisational beliefs and project timeframes, and their profound impact on long-term project success. This research stands out by deeply analysing three diverse, globally-spanning projects, showcasing the universal applicability and transformative potential of strategic alignment. The insights gathered reveal that aligning organisational beliefs with team strategies significantly offsets the benefits of diverse team compositions or geographic considerations in ensuring project success. Intriguingly, we highlight a prevalent industry oversight—prioritising short-term goals at the expense of long-term strategic alignment, thus uncovering a critical area for improvement. Utilising the Design Science Research (DSR) methodology, we developed and validated our artefact through iterative cycles of design, evaluation, and refinement. This approach ensured the practical relevance and rigour of the artefact, which was tested in real-world settings to assess its effectiveness in enhancing team alignment and project outcomes. The study not only bridges the gap between theory and practice but also introduces an innovative framework for continuous assessment and enhancement of team dynamics. By focusing on belief systems, we provide organisations with a powerful tool to navigate the complexities of temporary alliances, ensuring shared understanding and strategic vision alignment throughout all project stages. Future research should explore the impact of technological advancements and cultural diversity on team alignment within Project-Based Alliances. Social implications of this research include fostering a collaborative culture, promoting ethical practices, and supporting sustainable development in the construction industry.